Dispersal of plating wastes and sewage contaminants in ground water and surface water, South Farmingdale-Massapequa Area, Nassau County, New York - Perlmutter, Nathaniel M. | Lieber, Maxim (Contribution to the hydrology of the United States. / Washington, 1970)
The latest in a series of four studies made in southearstern Nassau County N. Y., from about 1949 to 1964 affirded an unusual opportunity to compare the dispersal of heavy-metal ions discharged into ground water in the metal-plting-waste efluent from an industrial plant with the dispersal of detergents from several hundred domestic cesspools and septic tanks. The contamination ground water is moving throug highly permeable beds of sand and gravel of the upper glacial aquifer. the quality of the water in the underlying Magothy aquifer, a major artesian unit, is apparently unaffected by these contaminants.